Transient, Isolated Head Tremor in “Unaffected” Individuals: Is Essential Tremor an Even More Prevalent Disease Than We Suppose? - Louis, Elan D.; Meyers, James H.; Cristal, Ashley D.; Patel, Amar; Tinaz, Sule; Pullman, Seth L.; Clark, Lorraine N.; Ottman, Ruth; Factor-Litvak, Pam (Frontiers in Neurology, 2018)
Background: Mild and transient head tremor may sometimes be observed in otherwise tremor-free relatives of essential tremor (ET) cases, although its prevalence is unclear. A diagnostic question is whether this transient, isolated head tremor, often observed as no more than a wobble, is an early manifestation of ET or whether it is a normal finding. A direct comparison with controls is needed. Methods: 241 first-degree relatives of ET cases (FD-ET) and 77 spousal controls (Co) were enrolled in a study of ET. Each underwent a detailed evaluation that included a tremor history and videotaped neurological examination. None of the enrollees reported tremor, had a prior diagnosis of ET, or had significant tremor on screening spirals. All videotaped examinations were initially reviewed by a movement disorder neurologist blinded to subject type, and among those with head tremor on examination, co-reviewed by two additional movement disorders neurologists. Results: Twenty-six (10.8%, 95% Confidence interval [CI] = 7.5% - 15.3%) of 241 FD-ET vs. 2 (2.6%, 95% CI = 0.7% - 9.0%) of 77 Co had isolated, transient head tremor (odds ratio = 4.54, 95% CI = 1.05 – 19.57, p = 0.04). No enrollee had significant upper extremity tremor and none met inclusion criteria for ET based on the presence of upper extremity tremor. With one exception, head tremor occurred during or after phonation. It was always transient (generally a single back and forth wobble) and rare (observed briefly on one or two occasions during the videotaped examination) and had a faster frequency, lower amplitude and a different quality than voluntary head shaking. Conclusion: The basis for the observed isolated head tremor is unknown, but it could be an early feature of ET in ET families. Indeed, one-in-ten otherwise unaffected first-degree relatives of ET cases exhibited such tremor. To a far lesser extent it was also observed in “unaffected” controls. In both, it is likely a sign of early, emerging, undiagnosed ET, although follow-up studies are needed to confirm this. If it were ET, it would indicate that the prevalence of ET may be considerably higher than previously suspected.